Development of Critical Thinking Skills Instruments : Cases for Essay Tests - Nurkhairo Hidayati; Suryanti Suryanti; Restesa Rahmayumita; Selvira Aisya (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2024)
This research aims to develop a rubric used to assess students’ critical thinking. This rubric refers to aspects of Ennis' critical thinking. The research method begins with determining the scope of the rubric so that an initial version of the rubric can be prepared. An initial version of the rubric received peer review. Next, the rubric was tested to assess critical thinking tests with essay-type questions. Data analysis was carried out using Cohen's kappa, while aspects of the critical thinking rubric were analyzed descriptively. The research results show that each aspect of critical thinking has been equipped with descriptors that can be used by raters. The level of reliability based on the kappa value of agreement is quite good, which means that different raters can use the rubric consistently. The value of agreement in the basic clarification aspect is 0.33 (fair), bases for a decision (0.571 in the moderate category), inference (0.455, moderate category), advanced clarification (0.250, fair category, supposition and integration (0.250, fair category), and strategies and tactics (0.182, poor category). Then, it can be concluded that the critical thinking rubric developed can be used to assess critical thinking abilities. As a recommendation, of course, this rubric cannot fulfill all types of critical thinking questions tested. It is also necessary to develop rubrics for question types other than essays to accommodate the wider need for critical thinking rubrics.